Research on the Limitations of Bone Age Assessment in Confirming the Age of Criminal Responsibility - Wenxi Deng (Studies in Law and Justice, 2025)
Bone age assessment is a technical means to observe the growth age of human beings by utilizing biological laws. At present, there are identification methods such as the atlas method, the scoring method, and the CHN method. However, bone age assessment has limitations in accuracy when it comes to confirming the age of criminal responsibility, is ambiguous in terms of the basis for legal application, has difficulties in coordinating with other evidence and in cross-regional and cross-jurisdictional applications, and also has problems such as chaotic qualifications of institutions and personnel and a lack of unified standards. Therefore, bone age assessment can only serve as an auxiliary reference to corroborate or supplement other evidence chains, and can only become the basis for age determination under extreme circumstances.